Preparation of Graduate Automotive Teachers for the World of Work in Kenya - Ronoh , Jonah Kipyegon; Okinyi , Herbert Dimo; Wanyonyi , John Simiyu (African Journal of Education,Science and Technology (AJEST), 2013)
Automotive teacher education and training in Kenya is aimed at preparing accomplished teachers to facilitate the learning process in secondary and post-secondary Technical and Vocational Education and Training(TVET) institutions offering power mechanics and automotive engineering respectively. This involves imparting the necessary knowledge and skills both in pedagogy and discipline content. This study assessed the adequacy in preparation of the graduate automotive teachers from University of Eldoret for the world of work. Areas considered were the knowledge and skills they acquired during training and what is required of them in the world of work and their job performance at the workplaces. The study employed descriptive survey design and data was collected through questionnaires, interviews and document analysis. Respondents were teachers‘ supervisors in the work places, graduate automotive teachers who had undergone the training and teaching in TVET institutions and fourth year automotive teacher trainees in the University. Data was analyzed using descriptive statistics with the help of Statistical Package for Social Scientists (SPSS). Content analysis was also applied in analyzing data from the documents. The findings reveal that there is some mismatch between the training acquired and that which is required in the world of work. In addition, the job performance of graduate automotive teachers is not in phase with the requirements of the work place. More is required of them than what they learn. The study recommends a review of the teacher training curriculum to reflect the additional content in the revised Kenya National Examination Council (KNEC) Modular syllabus in TVET institutions besides strengthening proper collaboration with the TVET institutions and the automotive industry in the face of changing technological trends.